Pengaruh Harga dan Fasilitas Terhadap Keputusan Berkunjung di Batu Love Garden (BALOGA) Kota Batu - Ramadhien, Yuris Zetta; Nurtjahjani, Fullchis; Zaini, Achmad (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
This study aims to learn about the influence of price and facilities on visiting decisions at Batu Love Garden (BALOGA) Batu City. The data type in this study is quantitative, with the population who were the visitors of Batu Love Garden (BALOGA) Batu City with a sample of 100 respondents. The data analysis techniques include validity and reliability test, classical assumptions, and simple regression analysis. In this case, price and facilities is the independent variable, and visiting decisions are the dependent variable. The result of this study suggest that price and facilities had a positive and significant effect on visiting decisions.